Native American Stories as Scientific Investigations of Nature: Indigenous Science and Methodologies - McCool, Calandra (My University, 2016)
Scientific knowledge is a global pursuit, one that takes on many different guises across cultures. This thesis argues that indigenous peoples have and had their own, independently developed forms of scientific knowledge, that are interwoven into stories that have been passed down for generations. I will share stories from my own tribe, the Potawatomi. Recognizing that Native American stories are tapestries of different types of knowledge—spiritual, scientific, and cultural— and that these knowledges cannot be extricated from one another, Native American science is neither directly comparable nor commensurable with Western, colonial, atheistic science. Rather, it has its own complex epistemology that must be recognized and valued for its difference, but also legitimated as having the same spirit of empirical understanding, as Western science.
Keywords: Native American Studies.; History of Science.; History, United States.; p